Relationship between Organizational Justice and Organizational Citizenship Behavior in Iran - Rangriz, Hassan (International Journal of Asian Social Science, 2012)
Purpose – The purpose of this paper is to examine the, relationship between organizational justice and organizational citizenship behavior among 186 experts of Ministry of Economic Affairs and Finance (MEAF) in Iran. Design/methodology/approach – The papers develops a research model based on current literature and then test this model in MEAF selected from 18 Ministry, public sector in Iran. Statistics society consists of 186 experts include assistant of general managers in both personnel affairs and welfare and domestic payments department, and also professionals, managers and deputy of personnel affair and department of organization and methods in MEAF. The sample size provided based on "Cohan- Morgan- Korjsay" is 186 experts which has been determined with descriptive methods. For data analyzing we used analysis of Kolmogorov-Smirnov's, analysis of correlation, and analysis of variance test. Findings – The results indicate that we found that there is positive relationship between organizational justice and OCB. Research limitations/implications – This study could benefit from a large sample from public sector and replication in more Ministries. Practical implications – The paper offers practical suggestions to the public sector and management in general on how to manage the organizational justice effects on OCB. Originality/value – This paper has tried to provide an inclusive understanding about the relationship between organizational justice and OCB in the MEAF in Iran. Since there was a lack of such research in an Iranian context, this paper can provide theoretical basis for future researches as well as practical implications for managers and the professionals.